Future developments of radiation tolerant sensors based on the MALTA architecture. (15th March 2023) - Dobrijević, D.; Allport, P.; Asensi, I.; Berlea, D.; Bortoletto, D.; Buttar, C.; Dachs, F.; Dao, V.; Denizli, H.; Sanz de Acedo, L.F.; Gabrielli, A.; Gonella, L.; et al.
Abstract: The planned MALTA3 DMAPS designed in the standard TowerJazz 180 nm imaging process will implement the numerous process modifications, as well as front-end changes in order to boost the charge collection efficiency after the targeted fluence of 1 × 10 15 1 MeV neq /cm 2 . The effectiveness of these changes have been demonstrated with recent measurements of the full size MALTA2 chip. With the original MALTA concept being fully asynchronous, a small-scale MiniMALTA demonstrator chip has been developed with the intention of bridging the gap between the asynchronous pixel matrix, and the synchronous DAQ. This readout architecture will serve as a baseline for MALTA3, with focus on improved timing performance. The synchronization memory has been upgraded to allow clock speeds of up to 1.28 GHz, with the goal of achieving a sub-nanosecond on-chip timing resolution. The subsequent digital readout chain has been modified and will be discussed in the context of the overall sensor architecture.